Domestic and Family Violence and Private Family Report Writing Practice in the Australian Family Law System: A Study - Samantha Jeffries; Helena Menih; Zoe Rathus AM; Rachael Field (Bond Law Review)
In Australia, family reports are an influential expert assessment of a family usually undertaken in contentious family law parenting matters by social workers or psychologists, known as family report writers. This article presents findings from in-depth interviews with 10 private family report writers about their experience of undertaking assessments, particularly in cases where domestic and family violence is alleged. The study reveals a number of concerns that mirror the findings of previous Australian and international research in this area. For example, concerns were raised about the quality and efficacy of training and access to other resources, professional isolation, the efficacy of the family report assessment process, and divergence in understandings of domestic and family violence. A critical issue raised in the study relates to the pro-contact and co-parenting culture of the Australian family law system, which can significantly impact the family report writing process and may have repercussions for the safety of victims of domestic and family violence and their children. Responding to and drawing from the family report writers’ lived experiences, we offer suggestions for reform that aim to improve the efficacy of the family report assessment process and therefore the justice and safety of outcomes in matters where a family report is deemed necessary.